Jenis-Jenis Belalang (Orthoptera: Ensifera di dusun III desa Rambah Hilir Tengah Kecamatan Rambah Hilir Kabupaten Rokan Hulu - Syahlan, Sutrisno (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This study aims to determine the types of grasshoppers (Orthoptera: Ensifera) contained in the hamlet III village Rambah Hilir Tengah District of Rambah Hilir Rokan Hulu Regency. This study was conducted from September to December 2015 with a survey method to the study site directly. Grasshopper obtained was then identified by describing the types based reference source. Results of the study found a grasshopper with 2 families, 9 subfamily, 13 genera and 16 species. As for the types of grasshoppers that are Conocephalus maculatus, C. melaenus, Conocephalus sp, Elimaea sp, Euscyrtus concinnus, Hexacentrus unicolor, Itara sp, Loxoblemmus parabolicus, Mecopoda elongata, Nisitrus vittatus, Phaulula sp, sp Psyrana, Teleogryllus emma, Teleogryllus sp, Velarifictorus sp and Xabea sp.